PEMANFAATAN TEKNOLOGI E-COMMERCE DALAM MENINGKATKAN PEMASARAN PRODUK KREATIF: STUDI KASUS TOKO ONLINE MESSI SHOP DI PEKALONGAN: UIN K.H ABDURRAHMAN WAHID PEKALONGAN - Pramono, Sigit; Ismanto, Kuat; Nur Khasanah, Titi (Jurnal Ekonomi Bisnis Manajemen dan Akuntansi (JEBISMA), 2024)
The digital transformation offers significant opportunities for small and medium enterprises (SMEs) to expand market reach through e-commerce, enabling broader consumer access and enhancing competitiveness. The success of e-commerce implementation in SMEs is often influenced by the uniqueness of products that can attract consumer interest. Messi Shop, an online store based in Pekalongan, utilizes e-commerce to market local specialty products such as daster dresses, chino shorts, chino pants, and children's clothing. This study aims to identify Messi Shop's use of Shopee and TikTok Shop platforms to enhance product marketing through a qualitative case study approach, employing observation and interview techniques.The findings indicate that Messi Shop leverages engaging visual content, innovative promotional strategies, and active customer interaction to increase product visibility on e-commerce platforms. However, several challenges are encountered, including intense competition, consumer behavior dynamics, and the need for continuous technological adaptation. This study concludes that e-commerce utilization positively impacts Messi Shop's product marketing and offers practical recommendations for other SMEs seeking to develop digital marketing.